167k views
3 votes
How to differentiate y=x^n using the first principle. In this question, I cannot use the rule of differentiation. I have to do the old fashioned way. How do I do it?​

1 Answer

6 votes

By first principles, the derivative is


\displaystyle\lim_(h\to0)\frac{(x+h)^n-x^n}h

Use the binomial theorem to expand the numerator:


(x+h)^n=\displaystyle\sum_(i=0)^n\binom nix^(n-i)h^i=\binom n0x^n+\binom n1x^(n-1)h+\cdots+\binom nnh^n


(x+h)^n=x^n+nx^(n-1)h+\frac{n(n-1)}2x^(n-2)h^2+\cdots+nxh^(n-1)+h^n

where


\dbinom nk=(n!)/(k!(n-k)!)

The first term is eliminated, and the limit is


\displaystyle\lim_(h\to0)\frac{nx^(n-1)h+\frac{n(n-1)}2x^(n-2)h^2+\cdots+nxh^(n-1)+h^n}h

A power of
h in every term of the numerator cancels with
h in the denominator:


\displaystyle\lim_(h\to0)\left(nx^(n-1)+\frac{n(n-1)}2x^(n-2)h+\cdots+nxh^(n-2)+h^(n-1)\right)

Finally, each term containing
h approaches 0 as
h\to0, and the derivative is


y=x^n\implies y'=nx^(n-1)

User Imposeren
by
5.3k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.